Impact of interleukin 28B rs12979860 C/T polymorphism on severity of disease and response to treatment in hepatitis delta - Ispirologlu, Murat; Bahcecioglu, Ibrahim Halil; Demirel, Ulvi; Yalniz, Mehmet (J Infection Developing Countries, 2017)
Introduction: Pegylated-interferon alpha (Peg-IFN alpha) is the therapy most commonly used to treat chronic hepatitis delta virus (HDV) infection. In the present study, we planned to investigate effect of IL28B polymorphism on response to Peg-IFN alpha therapy and disease progression in patients with chronic HDV. Methodology: A total of 47 patients who received Peg-IFN alpha therapy for at least one year were investigated. The patients were divided into three groups based on their response to treatment: sustained viral response (SVR) (32%), unresponsive (53%), and relapse (15%). The groups were compared in terms of age, gender, blood biochemistry (albumin, total bilirubin, lactic acid dehydrogenase, ALT, AST, ALP, GGT), complete blood count, HBeAg, HBsAg, HBV-DNA, HDV-RNA, IL28B genotypes (CC, CT, TT), and results of liver biopsy. Results: Regarding the investigation of IL28B genotype, the prevalence of CC, CT, and TT showed no difference among the three groups. In the SVR group, the prevalence of CC was 53%, CT was 47%, but there was no patient with TT. In the unresponsive group, prevalence of CC was 52%, CT was 32%, and TT was 16%. In the relapse group, prevalence of CC was 43%, CT was 57%, but there was no patient with TT genotype. No significant difference was found among the groups with sustained response, no response, and relapse in terms of CC and CT polymorphisms (p > 0.05). Conclusions: No relationship was found between IL28B rs12979860 polymorphism and response to treatment and disease severity in patients with chronic HDV infection.
Keywords: Delta hepatitis; interleukin 28B; interferon